2021
DOI: 10.1155/2021/8861074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Antibiotic-Resistant Genes in Pseudomonas aeruginosa from Nonclinical Environment: Public Health Implications in Mthatha, Eastern Cape Province, South Africa

Abstract: Evaluation of resistant profiles and detection of antimicrobial-resistant genes of bacterial pathogens in the nonclinical milieu is imperative to assess the probable risk of dissemination of resistant genes in the environment. This paper sought to identify antibiotic-resistant genes in Pseudomonas aeruginosa from nonclinical sources in Mthatha, Eastern Cape, and evaluate its public health implications. Samples collected from abattoir wastewater and aquatic environment were processed by membrane filtration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…In 2016, Sharma et al (33) discovered that amikacin (18.2% ) and ciprofloxacin (31.7%) were the most effective drugs for routine use among the P. aeruginosa strains studied (34). Similarly, Hosu et al reported 16.7 and 22.2% resitance for amikacin and ciprofloxacin respectively (13). In accordance with our findings, Mobaraki in Iran reported increased resistance for both amikacin and ciprofloxacin from the year 2007 to 2014 (35).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In 2016, Sharma et al (33) discovered that amikacin (18.2% ) and ciprofloxacin (31.7%) were the most effective drugs for routine use among the P. aeruginosa strains studied (34). Similarly, Hosu et al reported 16.7 and 22.2% resitance for amikacin and ciprofloxacin respectively (13). In accordance with our findings, Mobaraki in Iran reported increased resistance for both amikacin and ciprofloxacin from the year 2007 to 2014 (35).…”
Section: Discussionsupporting
confidence: 83%
“…The unreasonable administration of antibiotics in both human medicine and animal production for growth-promoting purposes, metaphylaxis, and prophylaxis have nourished the proliferation, spread of antibiotic-resistant bacteria, and resistance genes. Such an uncontrolled and random use of antibiotics increased public health and environmental risks (13). And also it is difficult to cure the patients whose infections are resistant to conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to some studies in Iran, bacterial isolates in our study showed more resistance to imipenem, lower resistance to amikacin and gentamicin and similar resistance to cefepime ( 30 ). In another study, isolates of P. aeruginosa revealed 50%, 63.9%, 16.7%, 8.3%, and 16.7% resistance to imipenem, cefepime, amikacin, tobramycin, gentamicin, respectively which is lower than the current study ( 31 ). Brzozowski et al reported lower rate of resistance to imipenem and cefepime and higher rate of resistance to tobramycin, amikacin, and gentamicin ( 32 ).…”
Section: Discussioncontrasting
confidence: 78%
“…Many reports have indicated that the resistance epidemiology is global and spreads through nations and across borders ( 46 ). Evaluation of resistant profiles and detection of antimicrobial-resistant genes of bacterial pathogens in the microbial inoculants is imperative to assess the probable risk of dissemination of resistant genes in the environment ( 47 ). The present study proved that HTS can be an effective approach in the safety and compliance of imported microbial inoculants.…”
Section: Discussionmentioning
confidence: 99%